2012
DOI: 10.1038/ejcn.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Neural effects of green tea extract on dorsolateral prefrontal cortex

Abstract: BACKGROUND/OBJECTIVES: Green tea is being recognized as a beverage with potential benefits for human health and cognitive functions. In vivo studies provide preliminary evidence that green tea intake may have a positive role in improving effects on cognitive functions. We aimed to examine the neural effects of green tea extract on brain activation in humans. SUBJECTS/METHODS: Functional magnetic resonance imaging was recorded while 12 healthy volunteers performed a working memory task following administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
(31 reference statements)
2
30
0
Order By: Relevance
“…Furthermore, green tea extract consisting of polyphenols, particularly catechins such as EGCG, caffeine, and theanine share an overlap in activity of at least one biochemical pathway, the N-methyl-D-aspartate receptor (NMDAR) pathway. Along this line, beneficial effects of green tea on cognitive functioning [151], in particular, on working memory processing at the neural system level suggested changes in short-term plasticity of parieto-frontal brain connections [152]. Additionally, evidence was found that the insulin sensitizer pioglitazone in a double-blind placebo-controlled study in 40 patients with major depression showed superiority over placebo during the course of the trial.…”
Section: Experimental Medications Focusing Primarily On Metabolic Aspmentioning
confidence: 93%
“…Furthermore, green tea extract consisting of polyphenols, particularly catechins such as EGCG, caffeine, and theanine share an overlap in activity of at least one biochemical pathway, the N-methyl-D-aspartate receptor (NMDAR) pathway. Along this line, beneficial effects of green tea on cognitive functioning [151], in particular, on working memory processing at the neural system level suggested changes in short-term plasticity of parieto-frontal brain connections [152]. Additionally, evidence was found that the insulin sensitizer pioglitazone in a double-blind placebo-controlled study in 40 patients with major depression showed superiority over placebo during the course of the trial.…”
Section: Experimental Medications Focusing Primarily On Metabolic Aspmentioning
confidence: 93%
“…It influences cell survival through down-regulation of pro-apoptotic genes (He et al 2011) and promotes neural progenitor cell proliferation (Levites et al 2002a). Green tea extract has also been shown to enhance the neuronal activity in the prefrontal cortical areas of brain concerned with processing of working memory (Borgwardt et al 2012).…”
Section: Tea Has Anti-alzheimer and Anti-parkinsonism Activitymentioning
confidence: 99%
“…The memory traces could be stabilized during the experimental sessions which helped BT consumers to retrieve the words [42]. A revious study [17] suggest that caffeine alters neuronal activity in the DLPFC (dorsolateral Pre-Frontal Cortex) during performance on a working memory task [38]. Additionally, our study showed that this effect might already had at caffeine dose of less than 70 mg.…”
Section: Discussionmentioning
confidence: 65%
“…Caffeine at a dose of 200-250 mg improves attention in visual search task [16]. Functional magnetic resonance imaging (fMRI) study reported that caffeine alters neuronal activity in the DLPFC (dorsolateral Pre-Frontal Cortex) on working memory task [17]. Caffeine also modulates neuronal activity [18].…”
Section: Introductionmentioning
confidence: 99%